THE HISTORY OF THE DEVELOPMENT OF THE NATIONAL CRAFT (TEXTILE AND SEWING) IN THE FERGHANA VALLEY (END OF THE XIX CENTURY - BEGINNING OF THE XX CENTURY) - Noila Obobakirovna Khayitboeva, (Galaxy International Interdisciplinary Research Journal, 2022)
In the article has been analyzed the history of the development of national crafts (textiles and tailoring) in the Ferghana Valley in detail with the help of scientific literature on the example of the end of the 19th - beginning of the 20th century.